Evidence of Natural Zika Virus Infection in Captive Cervid Species in Brazil - dos Santos, Fabíola de Souza Lemes; de Oliveira, Solange; Nogueira Romaldini, Adriana Hellmeister de Campos; Shimozako, Helio Junji; Freire, Bianca Castro; Mazzoni Baldini, Maria Helena [UNESP]; Barbanti Duarte, Jose Mauricio [UNESP]; Zanetti, Eveline Dos Santos [UNESP]; Okuda, Liria Hiromi (Wildlife Disease Association, 2024)
As part of an epidemiologic study of the Zika virus (ZIKV) in deer (Cervidae), samples from 56 captive deer in south and southeastern Brazil were tested for evidence of ZIKV. Three samples were positive using reverse-transcription quantitative PCR, although no samples were positive by virus isolation.